Application of airborne scanning laser altimetry to the study of tidal channel geomorphology - Lohani B.; Mason D.C. (My University, 2025)
Tidal channels play a fundamental role in the hydrodynamic and morphological processes operating within a tidal basin. Conventional means of mapping intertidal zones are either too cumbersome or do not provide sufficient information for accurate quantitative measurements of the channels. This paper describes the use of airborne scanning altimetry (light detection and ranging - LiDAR) for studying tidal channel geomorphology. The main emphasis is on developing a technique for extracting tidal channels from LiDAR data. Some common existing techniques of fluvial channel extraction are evaluated with LiDAR data of tidal basins and found moderate in performance. A semiautomatic approach is proposed which has a performance better than that of existing techniques. This approach is realised using an adaptive height thresholding technique to locate channel fragments. A channel joining mechanism then connects the channel fragments using a weighted distance transform. The paper also describes briefly an automatic procedure to carry out measurements on the basin image and derive geomorphological parameters such as drainage density. The results obtained illustrate differences in the geomorphology of tidal and terrestrial basins. © 2001 Elsevier Science B.V. All rights reserved.